2012
DOI: 10.1186/1754-9493-6-18
|View full text |Cite
|
Sign up to set email alerts
|

Renal tumors and second primary pancreatic tumors: a relationship with clinical impact?

Abstract: BackgroundThe occurrence of synchronous or metachronous renal cell carcinoma and pancreatic tumors has been described only in a few cases in the scientific literature. The study of double primary cancers is important because it might provide understanding of a shared genetic basis of different solid tumors and to detect patients at risk for secondary malignancy.MethodsIn a combined analysis of patient registries from University Departments of Urology and Visceral Surgery, 1178 patients with pancreatic tumors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…In addition, the most common locations of associated double primary tumors in the present study were found in the stomach (21.5%), colorectum (20.7%), lung (14.9%), and thyroid (10.7%). Conversely, the most common locations of associated double primary tumors in previous reports include stomach (n=51), thyroid (n=35), lung (n=22), and colorectum (n=20) ( S6 Table ) [ 8 , 12 , 14 - 17 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the most common locations of associated double primary tumors in the present study were found in the stomach (21.5%), colorectum (20.7%), lung (14.9%), and thyroid (10.7%). Conversely, the most common locations of associated double primary tumors in previous reports include stomach (n=51), thyroid (n=35), lung (n=22), and colorectum (n=20) ( S6 Table ) [ 8 , 12 , 14 - 17 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gerdes and colleagues reported 13 double primary cancers among 69 pancreatic cancer cases (18.8%), and they observed no differences in clinical parameters including OS differences between patients with pancreatic cancer only and pancreatic cancer patients with additional primary tumors [ 9 ]. Previously, Muller et al [ 14 ] evaluated 16 synchronous or metachronous renal cell carcinomas and pancreatic cancers and they observed no survival difference between 1,178 pancreatic cancer only patients and 16 pancreatic cancer with renal cell carcinoma (median survival time, 15.9 months vs. 12.6 months). In the present study, we observed only three pancreatic cancer cases with synchronous or metachronous renal cell carcinomas, and no OS difference was observed between pancreatic cancer patients with renal cell carcinoma and those with pancreatic cancer only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although pancreatic and kidney cancers are known to be independent, a crucial step in the diagnosis process of synchronous MPT is to eliminate a possible connection between the two different tumors [5]. Interesting genetic analysis of patients with concomitant pancreatic and renal cancers demonstrated microsatellite instability and mutations of codon 12 of k-ras gene [6,7]. Overall, the management plan of synchronous tumors is dictated by the staging of each primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggest a rising incidence of multiple primary malignancies in recent years, largely attributable to increased lifespan and cancer survivorship . Research into patients with PDAC and concurrent extra‐pancreatic malignancies outside the scope of hereditary cancer syndromes is limited and is reported most frequently in the form of case reports . In this study, we aimed to evaluate our experience with patients diagnosed with synchronous pancreatic and extra‐pancreatic malignancies who underwent pancreatic resections.…”
Section: Introductionmentioning
confidence: 99%